The ferruginous chert formations of Notre Dame Bay, Newfoundland - Sampson, Edward, b. 1890. ([Chicago, 1923)
"Reprinted from the Journal of geology, vol. xxxi, no. 7, October-November, 1923." Cover title. Thesis (Ph. D.)--Princeton University, 1920. Mode of access: Internet.